PENGARUH PH PADA PENURUNAN KADAR THORIUM DALAM LIMBAH MENGGUNAKAN PROSES ELEKTROKOAGULASI DENGAN ELEKTRODA ALUMUNIUM DAN TEMBAGA - Prayitno; Ridantami, Vemi; Mulyani , Indah Muji Mulyani (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Reduction of thorium level by electrocoagulation process has been done. Electrocoagulation process is a method used in waste management, which is based on the use of electrodes with potential difference to produce coagulant. One of the process parameters in electrocoagulation is pH. This study aims to determine the effect of pH on the electrocoagulation process in order to lower the thorium level. The method used was batch electrocoagulation process in electrocoagulator tub of 22.5 × 14.5 × 20 cm dimension. The electrodes used were aluminum and copper of 20 × 20 cm2 size with active surface area of 250 cm2. Electrodes were installed in parallel with 1 cm distance between the electrodes. The electrocoagulation process was carried out with a working voltage of 2 V for 60 minutes. Sampling was done every 5-minute interval to prepare samples for subsequent thorium level analysis and pH measurement. The results show changes in pH value during the electrocoagulation process. Such changes result in the concentration change, which was indicated by coagulant separation efficiency. The separation efficiency of aluminum electrode was 98.06%, which was indicated by an increase in thorium level from the initial value of 439.274 ppm to 8.503 ppm within 5 minutes at a pH of 7.38. The copper electrode shows 96.35% efficiency in reducing thorium level from the initial value of 439.274 ppm to 16.015 ppm within 5 minutes at a pH of 7.29. Both electrodes used in the electrocoagulation processes show high separation efficiency and significant increase in pH values within 5 minutes, suggesting that the formation rate of coagulants is rapid during 5 minutes.